ENHANCING STUDENTS SPEAKING SKILL THROUGH DEMONSTRATION STRATEGY AT BHINNEKA NUSANTARA VOCATIONAL HIGH SCHOOL BEKASI - Puput Amelia (Samudra Publisher, 2024)
Enhancing Students Speaking Skill Through Demonstration Strategy at Bhinneka Nusantara Vocational School Bekasi. This research aims to improve the speaking skills of Bhinneka Nusantara Vocational High School students by using the demonstration method. The subject of this research was used for all students at Bhinneka Nusantara Vocational High School Bekasi. This research used the Classroom Action Research Method. A method whose implementation was carried out to find out problems in the learning process and steps that teachers could use to improve the quality of learning. The research instruments are observations, questionnaires, exercise, daily tests and interviews. The data obtained from this Classroom Action Research Method is in the form of student activity and learning outcomes in each cycle. After carrying out the action, processing/analysis is then carried out on the data obtained from carrying out the action. Therefore, from this data it can be concluded that the application of the demonstration method can improve the speaking skills of Bhinneka Nusantara Vocational High School students.